Development of the conceptual framework (version 2.0) of the Multidimensional Digital Inclusiveness Index - Martins, Carolina Iglésias; Opola, Felix Ouko; Jacobs-Mata, Inga; Garcia Andarcia, Mariangel; Nortje, Karen; Joshi, Deepa; Singaraju, N.; Muller, A.; Christen, R.; Malhotra, A. (International Water Management Institute (IWMI). CGIAR Initiative on Digital Innovation, 2023)
The Multidimensional Digital Inclusiveness Index (MDII), initiated by CGIAR's Digital Innovation Initiative, has transformed from a theoretical concept to a practical tool for assessing digital inclusivity in various sectors. Its foundational document guides stakeholders in the Agri-Food, Water, and Land sectors, promoting collaboration and continuous improvement. The MDII is guided by eight principles, including accessibility, transparency, methodological rigor, adaptability, intersectionality, simplicity, flexibility, and clarity. It faces challenges such as complexity and diverse user needs, addressed through Artificial Intelligence (AI) integration, offline accessibility, and a participatory feedback approach. Evolving beyond an index, the MDII now offers multiple functions like certification, predictive analysis, and strategic guidance for digital innovation, using AI to meet future inclusiveness needs. The next steps for the MDII include conducting surveys to refine its framework, developing a comprehensive roadmap, and creating a prototype for stakeholder review.